Reservoir heterogeneity in the fluvio-deltaic outcrop analogue: A case study from the Surma Group, Bengal Basin, Bangladesh - Shariful Islam; Md Mostafizur Rahman; Shakhawat Hossain; Preety Kona Shaikh (Heliyon)
Multiscale sedimentological heterogeneities significantly influence the distribution of subsurface reservoir properties and contribute to reservoir compartmentalization. This study investigates sub-seismic scale heterogeneities within the fluvio-deltaic Surma Group successions - the primary hydrocarbon reservoirs in the Bengal Basin. Detailed outcrop-based facies and facies association analyses of the well-exposed analogues of these subsurface reservoirs in the northeastern Surma Basin were utilized to identify sedimentological heterogeneities and assess their implications for the entire Surma Group. Eleven lithofacies and five facies associations are identified, representing diverse depositional environments ranging from pro-delta to alluvial plain. The succession exhibits a progressive shallowing-upward trend, punctuated by two transgressive events in the lower and upper Surma Group. Five levels of heterogeneities (HL) are characterized: pro-delta mud (HL-I), tidal heterolithic deposits (HL-II and III), interbedded mud units in the delta front (HL-IV), and intercalated mud laminae and drapes (HL-V). These heterogeneities are closely related to the spatial distribution of the identified facies associations. The findings enhance the understanding of sub-seismic scale heterogeneities and production variations at different stratigraphic intervals within the Surma Group. The insights from this study will help in optimizing infill development wells and developing exploration strategies in similar fluvio-deltaic reservoirs globally.